The electronic structure of Au25 clusters: between discrete and continuous. Issue 31 (25th July 2016) - Katsiev, Khabiboulakh; Lozova, Nataliya; Wang, Lu; Sai Krishna, Katla; Li, Ruipeng; Mei, Wai-Ning; Skrabalak, Sara E.; Kumar, Challa S. S. R.; Losovyj, Yaroslav
Abstract : The electronic structure of ligand-stabilized Au25 clusters can be switched between atomic-like and bulk-like upon altering the shells. Resonant photoemission reveals significant hybridization effects in the naked gold nanoclusters. Abstract : Here, an approach based on synchrotron resonant photoemission is employed to explore the transition between quantization and hybridization of the electronic structure in atomically precise ligand-stabilized nanoparticles. While the presence of ligands maintains quantization in Au25 clusters, their removal renders increased hybridization of the electronic states in the vicinity of the Fermi level. These observations are supported by DFT studies.